COLOUR QUALITY ENHANCED ON GOLDFISH JUVENILES THROUGH SHRIMP HEAD MEAL ENRICHED IN FEED - I Wayan Subamia; Nina Meilisza; Asep Permana (Indonesian Aquaculture Journal, 2013)
Goldfish (Carassius sp.) is the ornamental fish which has been managed its culture by fish farmers. The objective of the research is to improve the colour quality of goldfish juveniles through enrichment of feed using shrimp head meal as source of carotenoid. The research was conducted at The Research and Development Institute for Ornamental Fish Culture, Depok, using completely randomized design with four treatments of shrimp head meal ratio, 0% (control), 5%, 10%, and 15% in feed, the feed formulation contained isoprotein (30%), and isolipid (15%) and three replications of each treatment. Ten juveniles of Carassius sp. with body weight of (1.08±0.02 g) stocked in aquarium with water volumes of 20 L. The growth and colour quality in qualitative standard using TCF (Toca Colour Finder) were examined, while total carotenoid content on feed were measured by spectrophotometry method. The colour quality of goldfish were also measured at three of fins those were dorsal, ventral, and caudal. The result showed that no significant different on growth and survival rates among the treatments. Based on the present research, the optimal colour improvement to goldfish was by addition of 10% shrimp head meal in feed.